Catalytic upgrading of biopolyols derived from liquefaction of wheat straw over a high-performance and stable supported amorphous alloy catalyst. (15th January 2018) - Guo, Haijun; Zhang, Hairong; Chen, Xuefang; Zhang, Liquan; Huang, Chao; Li, Hailong; Peng, Fen; Huang, Qianlin; Xiong, Lian; Ouyang, Xinping; Chen, Xinde; Qiu, Xueqing
Graphical abstract: Highlights: Crude biopolyols were obtained from the liquefaction of wheat straw. Cu0.5 Ni1 Co1 B/H + -ATP catalyst was applied to upgrade the crude biopolyols. Carbonyl compounds were effectively removed by hydrogenation and cyclization. Reaction temperature had a positive effect on the upgrading of crude biopolyols. Cu0.5 Ni1 Co1 B/H + -ATP catalyst could be recycled five times without deactivation. Abstract: Post-refining of crude biomass liquefaction-derived polyols (biopolyols) to remove undesired carbonyl compounds is essential to improve the quality of biopolymers. One of the dominated carbonyl compounds in the crude biopolyols, butyl levulinate (BL), was hydrogenated to γ-valerolactone (GVL) over Cu-modified NiCoB amorphous alloy catalyst to explore a high-efficient hydrogenation upgrading catalyst. Cu0.5 Ni1 Co1 B catalyst with metallic Cu particle size of 10.2 nm and the highest BL conversion of 74.6% was supported on the acid-activated attapulgite (H + -ATP) material. The synergistic effect between acidic and hydrogenated active centers in Cu0.5 Ni1 Co1 B/H + -ATP catalyst was proved by NH3 -temperature programmed desorption (NH3 -TPD) to promote the conversion of carbonyl compounds compared to unsupported Cu0.5 Ni1 Co1 B catalyst. Reaction temperature also showed a positive effect on the removal of carbonyl compounds especially for the acids and their esters. Under the optimum reaction conditions (140 °C, 1.0 MPa), the relative content of carbonyl compounds in crude biopolyols showed an obvious decrease of 10.3%, while the hydroxyl number of biopolyols increased by 140 mg KOH/g. Gas chromatography–mass spectrometry (GC–MS) analysis results indicated that the conversion of ethylene glycol condensation products and their monoesters or diesters of acetic acid and propionic acid was the major reaction during the process of hydrogenation upgrading of crude biopolyols. Cu0.5 Ni1 Co1 B/H + -ATP catalyst also exhibited well stability for the aqueous-phase hydrogenation of crude biopolyols without deactivation in five times run.